Earthquake Nucleation Along Faults With Heterogeneous Weakening Rate - Lebihain, Mathias; Roch, Thibault; Violay, Marie; Molinari, Jean‐François (Geophysical research letters, 2021)
The transition from quasistatic slip growth to dynamic rupture propagation constitutes one possible scenario to describe earthquake nucleation. If this transition is rather well understood for homogeneous faults, how the friction properties of multiscale asperities may influence the overall stability of seismogenic faults remains largely unclear. Combining classical nucleation theory and concepts borrowed from condensed matter physics, we propose a comprehensive analytical framework that predicts the influence of heterogeneities of weakening rate on the nucleation length Lc for linearly slip‐dependent friction laws. Model predictions are compared to nucleation lengths measured from 2D dynamic simulations of earthquake nucleation along heterogeneous faults. Our results show that the interplay between frictional properties and the asperity size gives birth to three instability regimes (local, extremal, and homogenized), each related to different nucleation scenarios, and that the influence of heterogeneities at a scale far lower than the nucleation length can be averaged. Plain Language Summary Earthquakes occurs on fault. Faults are usually at rest, but they sometimes break and suddenly release a portion of the accumulated elastic energy during earthquake ruptures through radiated waves, which may harm populations and structures. Yet, the birth of earthquake (nucleation phase) is not an instantaneous process and may start with slow slip on the fault. Understanding precisely how this initial phase occurs is thus crucial in predicting earthquake motion. If geophysical models describe it well in an ideal case where the fault is made of the same exact material (homogeneous fault), the role of asperities, which are present from the millimetric rock grain scale to the kilometric tectonic plate scale, remains largely unclear. Here, we propose an extension of the nucleation theory to account for the role of each asperity scale in nucleating earthquakes. Our results show that an earthquake can be triggered by some seismogenic asperities as previously assumed, but that these “weak” asperities may not control its nucleation if they are small enough. In that case, we show that the birth of earthquakes along complex faults can be accurately studied within the traditional homogeneous nucleation theory. Key Points The nucleation length of heterogeneous faults with multiscale asperities of weakening rate can be predicted for slip‐dependent friction Our theory accounts for the transition in fault stability regimes from the traditional "weakest defect" theory to a homogenized behavior Only asperities larger than the nucleation length participate in the fault stability, while the influence of small asperities is averaged